Two decades of change in a Bangladeshi village - Briscoe, John (2001)
This description of a revisit to village Fatepur turns on its head several existing, stereotypical notions of what constitutes development in Bangladesh. The villagers' assessment of what counts - old-fashioned investments in water control and transport infrastructure, as principal agents of progress - is in striking contrast to opinions and facts cited by NGOs and accepted as reality by many donor institutions. More importantly progress has been possible, despite several extraneous contributing factors, due to the ingenuity and vitality demonstrated by the people. - Reproduced
Keywords: Rural development - Bangladesh; Rural areas - Bangladesh; Rural development